Governance structures, resource mobilization, and organizational performance of community forest enterprises: Evidence from China - Yiwen, Zhang (Forest policy and economics, 2024)
Community forestry enterprises (CFEs) have diverse governance structures impacting their organizational performance, while limited research has explored the drivers and impact of these diversified institutions. Adopting a comparative case approach, this study examines three types of CFE models in southern China—shareholding forest farms, community-corporation partnerships, and cooperative reforestation—to understand the selection of the CFE's governance structures and their impact on organizational performance from the resource mobilization perspective. In three cases, the ranking of overall performance from the highest to lowest is cooperative reforestation, shareholding forest farm, and community-corporation partnership. However, all three models have their advantages and limitations, and social capital and human capital are critical for all CEF types. This study showcases the institutional diversity of CFEs, offers insights beyond the archetypical distinctions of CFEs identified in the literature, and illuminates the complex effects of organizational structures on CFEs' organizational performance. These findings may guide CFEs in optimizing their institutional arrangements according to their unique circumstances. •Analyzes three distinct CFE models in southern China.•Explores CFE's diverse governance structures and their impact.•Uses resource mobilization lens to study CFE's performance.•Advocates direct democracy for improved decision-making.•Emphasizes legal and policy adaptations for CFEs.